ATROPINE 0.01% AS A POTENTIAL MYOPIA PREVENTION IN CHILDREN WITH DOSAGE EFFECTIVITY COMPARISON: A LITERATURE REVIEW - Ivan, Ignatius; Stella, Maureen Miracle; Santosa, Mariani (Jurnal Kedokteran YARSI, 2019)
Myopia (long-sightedness) is one of the many problems of vision disorder occurring around the world and being 1 in 5 eye conditions that becoming a priority at the World Health Organization's Global Intitiative for the Elimination of Avoidable Blindness. Many methods of preventing myopia development have been sought. Atropine is an alkaloid derived herbal plant Atropa belladonna which acts as a muscarinic acetylcholine receptor antagonist that has a strong nonselective competitive affinity on the five types of muskarinic acetylcholine receptors (M1-M5) that weaken the muscles of the ciliary and iris and causes the reduction of accommodation and the occurrence of pupil dilation. Recent research found that with the use of low dose atropine (0.01%), in addition to the side effects inflicted more minimal, effectiveness in the long time period shows better results. Until now, the  mechanism of atropine is still experiencing debate whether working on an accommodating or non-accommodating pathway. But recent research suggests the possibility of working mechanism of this drug is through a non-accommodating pathway i.e. on GABAergic, dopaminergic as well as involving nitric oxide (NO) role to help inhibit the progression of myopia. In research and advanced scientific studies, it can be researched regarding the pathways of atropine mechanism and its advantages and disadvantages at any dose of atropine given to myopia sufferers using the latest literature sources.